MMP7 cleaves remyelination‐impairing fibronectin aggregates and its expression is reduced in chronic multiple sclerosis lesions. Issue 8 (30th March 2018) - Wang, Peng; Gorter, Rianne P.; de Jonge, Jenny C.; Nazmuddin, Muhammad; Zhao, Chao; Amor, Sandra; Hoekstra, Dick; Baron, Wia
Abstract: Upon demyelination, transient expression of fibronectin precedes successful remyelination. However, in chronic demyelination observed in multiple sclerosis (MS), aggregates of fibronectin persist and contribute to remyelination failure. Accordingly, removing fibronectin (aggregates) would constitute an effective strategy for promoting remyelination. Matrix metalloproteinases (MMPs) are enzymes known to remodel extracellular matrix components, including fibronectin. Here, we examined the ability of MMPs to degrade fibronectin aggregates. Our findings reveal that MMP7 cleaved fibronectin aggregates resulting into a prominent 13 kDa EIIIA (16 kDa EDA)‐containing fragment. MMP7 was upregulated during lysolecithin‐induced demyelination, indicating its potential for endogenous fibronectin clearance. In contrast, the expression of proMMP7 was substantially decreased in chronic active and inactive MS lesions compared with control white matter and remyelinated MS lesions. Microglia and macrophages were major cellular sources of proMMP7 and IL‐4‐activated, but not IFNγ+LPS‐activated, microglia and macrophages secreted significant levels of proMMP7. Also, conditioned medium of IL‐4‐activated macrophages most efficiently cleaved fibronectin aggregates upon MMP‐activating conditions. Yet, coatings of MMP7‐cleaved fibronectin aggregate fragments inhibited oligodendrocyte maturation, indicating that further degradation and/or clearance by phagocytosis is essential. These findings suggest that MMP7 cleaves fibronectin aggregates, while reduced (pro)MMP7 levels in MS lesions contribute to their persistent presence. Therefore, upregulating MMP7 levels may be key to remove remyelination‐impairing fibronectin aggregates in MS lesions. Main Points: MMP7 cleaves remyelination‐impairing fibronectin aggregates. ProMMP7 levels are reduced in chronic MS lesions. IL‐4‐activated microglia and macrophages are major cellular source of proMMP7 and cleave fibronectin aggregates upon MMP‐activating conditions.